Pathophysiology of Major Depression by Clinical Stages - de Menezes Galvão, Ana Cecília; Almeida, Raíssa Nobrega; de Sousa, Geovan Menezes; Leocadio-Miguel, Mario André; Palhano-Fontes, Fernanda; de Araujo, Dráulio Barros; Lobão-Soares, Bruno; Maia-de-Oliveira, João Paulo; Nunes, Emerson Arcoverde; Hallak, Jaime Eduardo Cecilio; Schuch, Felipe Barreto; Sarris, Jerome; et al. (Frontiers in Psychology, 2021)
The comprehension of the pathophysiology of the major depressive disorder (MDD) is essential to the strengthening of precision psychiatry. In order to determine the relationship between the pathophysiology of the MDD and its clinical progression, analyzed by severity of the depressive symptoms and sleep quality, we conducted a study assessing different peripheral molecular biomarkers, including the levels of plasma C-reactive protein (CRP), serum mature brain-derived neurotrophic factor (mBDNF), serum cortisol (SC), and salivary cortisol awakening response (CAR), of patients with MDD (n = 58) and a control group of healthy volunteers (n = 62). Patients with the first episode of MDD (n = 30) had significantly higher levels of CAR and SC than controls (n = 32) and similar levels of mBDNF of controls. Patients with treatment-resistant depression (TRD, n = 28) presented significantly lower levels of SC and CAR, and higher levels of mBDNF and CRP than controls (n = 30). An increased severity of depressive symptoms and worse sleep quality were correlated with levels low of SC and CAR, and with high levels of mBDNF. These results point out a strong relationship between the stages clinical of MDD and changes in a range of relevant biological markers. This can assist in the development of precision psychiatry and future research on the biological tests for depression.